TRANSFORMING WASTE IN THE PHILIPPINES: CIRCULAR ECONOMY'S IMPACT ON BUSINESS AND ENVIRONMENT - SALVACION, Justine Marc; CAMPOS, Karl (Journal of process management and new technologies, 2024)
Circular economy’s (CE) increasing attention leads to many countries adopting it and became a policy tool to advance sustainability as stated in the research of (Padilla-Rivera et al., 2020). This study focused on how CE can impact both business and the environment specifically in the Philippines to address the notable lack of literature review focusing on this topic in the context of the Philippines. The research derived themes such as a lack of regulatory framework, strengthening and standardization for better implementation, and low awareness. The study showed that addressing these issues and fostering practices that promote sustainability and economic growth is essential. Lastly, this research provides a better view of how proper implementation of the CE can affect both business and the environment.
Keywords: Circular economy, Philippines, sustainability, business practices, environment